Self-generated and experimenter-provided negative income shock narratives increase delay discounting - Mellis, Alexandra M. (Exp Clin Psychopharmacol, 2018)
Reading experimenter-provided narratives of negative income shock has been previously demonstrated to increase impulsivity, as measured by discounting of delayed rewards. We hypothesized that writing these narratives would potentiate their effects of negative income shock on decision-making more than simply reading them. In the current study, 193 cigarette-smoking individuals from Amazon Mechanical Turk were assigned to either read an experimenter-provided narrative or self-generate a narrative describing either the negative income shock of job loss or a neutral condition of job transfer. Individuals then completed a task of delay discounting and measures of affective response to narratives, as well as rating various narrative qualities such as personal relevance and vividness. Consistent with past research, narratives of negative income shock increased delay discounting compared to control narratives. No significant differences existed in delay discounting after self-generating compared to reading experimenter-provided narratives. Positive affect was lower and negative affect was higher in response to narratives of job loss, but affect measures did not differ based on whether narratives were experimenter-provided or self-generated. All narratives were rated as equally realistic, but self-generated narratives (whether negative or neutral) were rated as more vivid and relevant than experimenter-provided narratives. These results indicate that the content of negative income shock narratives, regardless of source, consistently drives short-term choices.